PENGEMBANGAN JARINGAN DISTRIBUSI AIR BERSIH KECAMATAN PELING TENGAH - Sampe, Nober; Tunas, I Gede; Andiese, Vera Wim (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2013)
This study aims to provide an overview of the development planning of water distribution networks in the village of  Patutuki District   of   Peling Tengah,   considering   the region located in the coastal areas with limited of surface water sources, moreover the constriction and leakage in pipelines and water quality containing calcium or poor maintenance, so  the  flow  of  water  to  the  consumer  is reduced.  The scope  of study  is limited  to the analysis  of the availability  of water  discharge mainstay  as  one  of  the  water  sources  in  the village  Patutuki  using  FJ.  Mock  and  calculate the   domestic  water   supply   in   the   village   of Patukuki  District  of  Peling Tengah  depended on the number of  population. Furthermore, network planning distribution of domestic water in the service  area by gravity  through  the branching  system  and  closed  pipes.  For secondary data collection was carried out in the form  of meteorological  data,  population  data, topographic  data  and  the  data  of  land-use. Then calculate the water needs to be compared with the discharge  mainstay. The result is the minimum river discharge mainstay of Bebek River which is the main water source to meet water  needs in the area of service to 20 years .The maximum pressure meets the maximum permissible  limit  of 10 kg/cm2 and also meet the maximum  speed limit is a maximum  of 3 m3/sec.  For  the required  number  of plumbing needs in this plan that HDPE pipe ø 102 mm by 108 rods , PVC pipe ø 102 mm 33 rods , PVC pipe ø 76 mm 557 rods , and PVC pipe ø 51 mm 749 rods.   Keywords: water distribution networks, domestic water, Peling Tengah